If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14x+6=6x+4+3
We move all terms to the left:
14x+6-(6x+4+3)=0
We add all the numbers together, and all the variables
14x-(6x+7)+6=0
We get rid of parentheses
14x-6x-7+6=0
We add all the numbers together, and all the variables
8x-1=0
We move all terms containing x to the left, all other terms to the right
8x=1
x=1/8
x=1/8
| 12x+8=21-x | | 25=-3y=10 | | 8z=9z+6 | | 10x=14x= | | -2p+27+8p=5p-23 | | 2=-3d+(-4) | | 9(x=2)-3=3(3x+5) | | 8-7x=13x+12 | | 7-m/9=16 | | A=8/3(h-64) | | -2=-m/5=1 | | 5(c-6)=-5 | | 6=a/3-7 | | 8-5x=-3+14 | | -10=-5-a/2 | | 9x−6=3x+3 | | 5x+4+6x=40 | | 597=28x | | -5+2x^2=-7x+x^2-4 | | -18=5e-3 | | 6=6-2u | | 4(x+1)=4(2x+3) | | -8-2x=4x-4-3x^2 | | 14x7=x | | 3.5y−12=1.5(y−2 | | 1/2x=75 | | 10=20-2c | | -8x+3x^2=-18 | | 3(2x-8)=2(3x | | 4g+17=53 | | 31.67x=370 | | 5/9x-40=0 |